2013
DOI: 10.1089/dia.2012.0283
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable Adaptive Closed-Loop Control of an Artificial Pancreas Without Meal and Activity Announcement

Abstract: Background: Accurate closed-loop control is essential for developing artificial pancreas (AP) systems that adjust insulin infusion rates from insulin pumps. Glucose concentration information from continuous glucose monitoring (CGM) systems is the most important information for the control system. Additional physiological measurements can provide valuable information that can enhance the accuracy of the control system. Proportional-integral-derivative control and model predictive control have been popular in AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
133
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 32 publications
1
133
0
1
Order By: Relevance
“…18 In a pilot experiment, another team showed that the regulation of blood glucose was feasible in a closed-loop system without any meal announcement. 19 Another team reported that their MPC controller was at least as effective as conventional therapy in managing rises in blood glucose following breakfast. 20 The fuzzy-logic-based approach has been shown to also have the potentiality to identify meals that require special treatment, in a feasibility study where the mean detection time after meal consumption was 23 minutes and the mean peak postprandial glucose level was 224 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…18 In a pilot experiment, another team showed that the regulation of blood glucose was feasible in a closed-loop system without any meal announcement. 19 Another team reported that their MPC controller was at least as effective as conventional therapy in managing rises in blood glucose following breakfast. 20 The fuzzy-logic-based approach has been shown to also have the potentiality to identify meals that require special treatment, in a feasibility study where the mean detection time after meal consumption was 23 minutes and the mean peak postprandial glucose level was 224 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] A crucial element of any fully automated AP is a feedback control law that performs algorithmic insulin dosing that is effective and safe. A variety of such glycemia controllers have been proposed, e.g., based on model predictive control (MPC), [5][6][7][8][9][10] proportional-integral-derivative control, 11,12 fuzzy logic, 13 and adaptive neural networks. 14 The authors' group has been focusing increasingly on developing MPC strategies.…”
Section: Introductionmentioning
confidence: 99%
“…2 Most artificial pancreas (AP) control systems regulate BG concentrations in persons with T1D by using information from a continuous glucose monitor with little or no regard to physical activity levels. [3][4][5][6][7][8][9][10][11][12] Physical activity challenges the AP system as a disturbance that can lead to unsafe conditions such as hypoglycemia or hyperglycemia. 13,14 There have been limited studies where additional physiological signals are used in an AP system for the prevention of exercise-induced hypoglycemia.…”
mentioning
confidence: 99%
“…13,14 There have been limited studies where additional physiological signals are used in an AP system for the prevention of exercise-induced hypoglycemia. [10][11][12]15 In all of these studies, the classification of exercise type (ie, aerobic, anaerobic, mixed) was not considered.…”
mentioning
confidence: 99%
See 1 more Smart Citation